The influence of habitat structure on juvenile fish in a New Zealand estuary. (5th June 2013) - Parsons, Darren M.; Morrison, Mark A.; Thrush, Simon F.; Middleton, Crispin; Smith, Matt; Spong, Keren T.; Buckthought, Dane
Abstract Estuarine and sheltered coastal habitats that contain physical structure are potentially important nurseries for juvenile fish. Many of these structured habitats, however, are potentially vulnerable to stressors such as elevated turbidity. Quantifying the benefits that structured habitats provide to juvenile fish may therefore be an important step in the management process. We investigated the value of structured habitat for juvenile fishes in northeastern New Zealand, using artificial seagrass units (ASUs) with varying blade density. ASUs were predominantly settled by juvenile snapper (Pagrus auratus) and spotty (Notolabrus celidotus). The density of both snapper and spotty was greatest on ASUs with the highest blade density. For snapper, a gradient in abundance was present (with higher abundance closer to the harbour mouth), suggesting either a gradient in the supply of recruits or a potential recruitment shadow effect. The size distribution of juvenile snapper (12–70 mm fork length) was very similar on both sampling trips, despite the 2‐month interim period, suggesting an ontogenetic habitat shift dependent on size. The condition of juvenile snapper from ASUs with the highest blade density was also greater than the other ASU treatments. Overall, these results provide new empirical evidence that habitats with physical structure within shallow estuarine systems are important to early stage juvenile fishes such as snapper, and indicate that the location‐specific context of that habitat is also likely important.